2007
DOI: 10.1021/ja069095g
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Imine Derivatives (‘Synzymes') Accelerate Phosphate Transfer in the Absence of Metal

Abstract: The efficient integration of binding, catalysis, and multiple turnovers remains a challenge in building enzyme models. We report that systematic derivatization of polyethylene imine (PEI) with alkyl (C(2)-C(12)), benzyl, and guanidinium groups gives rise to catalysts ('synzymes') with rate accelerations (k(cat)/k(uncat)) of up to 10(4) for the intramolecular transesterification of 2-hydroxypropyl-p-nitrophenyl phosphate, HPNP, in the absence of metal. The synzymes exhibit saturation kinetics (K(M) approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
50
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 58 publications
1
50
1
Order By: Relevance
“…Following earlier work by Klotz and others,18–26 we have demonstrated in previous studies that environmental effects can also be exploited in water by using synthetic polymeric enzyme models (′synzymes′). Synzymes are based on a polyethylene imine (PEI) backbone that is functionalised combinatorially to create a microenvironment in which desolvation, dispersion interactions and specific medium effects support catalysis 2729. Synzyme libraries have been shown to contain efficient catalysts with rate accelerations up to 10 7 (in k cat / k uncat ) or 10 8 (in ( k cat / K m )/ k 2 ) and multiple turnovers 2729.…”
Section: Introductionmentioning
confidence: 99%
“…Following earlier work by Klotz and others,18–26 we have demonstrated in previous studies that environmental effects can also be exploited in water by using synthetic polymeric enzyme models (′synzymes′). Synzymes are based on a polyethylene imine (PEI) backbone that is functionalised combinatorially to create a microenvironment in which desolvation, dispersion interactions and specific medium effects support catalysis 2729. Synzyme libraries have been shown to contain efficient catalysts with rate accelerations up to 10 7 (in k cat / k uncat ) or 10 8 (in ( k cat / K m )/ k 2 ) and multiple turnovers 2729.…”
Section: Introductionmentioning
confidence: 99%
“…The guanidinium group itself may be especially suited to binding phosphate because of its ability to form two simultaneous hydrogen-bonding interactions with phosphate oxygens (12-15). However, mutagenesis studies in several enzymes have found that loss of the arginine side chain yields dramatic reduction in catalysis without apparent changes in substrate affinity, raising the possibility of specificity of the arginine interactions for transition state charge and/or geometry (8-11, 16).…”
mentioning
confidence: 99%
“…The low residual activity of non-metalated Au NP 1 presumably originates from the presence of protonated TACN-ligands, at neutral or acidic pH. [19] In this study, Cu 2+ and Cd 2+ metal ions were deliberately chosen for a number of reasons. Firstly, measurement of the catalytic activity as a function of the amount of Cu 2+ and Cd 2+ added to Au NP 1 showed that both metal ions activated the system for catalysis, reaching a maximum when a stoichiom- ], the rate acceleration was significantly higher for Au NP 1·Cu 2+ (9 times, red squares) than for Au NP 1·Cd 2+ (2.5 times, green squares) when compared to the background (Figure 1 b, dashed line).…”
mentioning
confidence: 99%